Transformasi Pemasaran Warung Berkah melalui Media Sosial dan Layanan Pesan Antar Online - Budiman, Johny; Jolin, Jolin (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Technology has become an important aspect of the business world as it is able to expand market reach, improve efficiency, and enhance competitiveness. Currently, many Micro, Small, and Medium Enterprises (MSMEs) have adopted technology to expand their businesses and promote their products. However, Warung Berkah has not yet adopted technology in its operations. Warung Berkah has been operating for nearly three years and has successfully provided a variety of culinary products to customers; nevertheless, despite its relatively long establishment, this MSME has not developed optimally. By developing social media accounts and implementing online ordering services, the Warung Berkah MSME is expected to grow further. The implementation process of this activity was carried out through interviews, observations, and documentation, and the results obtained after implementing the developed platforms indicate fairly positive outcomes, as evidenced by increased interaction on Warung Berkah’s social media pages. The expected impact of this activity is that the Warung Berkah MSME will continue to utilize digital-based promotional media through social media accounts and consistently make use of online ordering services.